(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sustainable Development Goals are a wake-up call against the earth and well-being of people around the world. Sustainable Development Goals have 17 major goals and 169 targets, its aim is to reshape our world by 2030 and it was agreed by 193 member countries of United Nations by 2015. According to the Sustainable Development Report 2022 India’s overall rank is 121 which indicate that still we need to take necessary actions which lead to reach the Sustainable Development Goals. According to this report, Since the 163 countries adapted Sustainable Development Goals the average growth rate was 0.5 per year. Still, after COVID-19 the average progress rate has declined by 0.1 per year. Hence, we need to create awareness among people all over the nation about Sustainable Development Goals and the necessity of Sustainable Development.